Optical solitons to the resonant nonlinear Schrodinger equation with both spatio-temporal and inter-modal dispersions under Kerr law nonlinearity - Bulut, Hasan; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet (Elsevier Gmbh, 2018)
This study uses the extended sinh-Gordon equation expansion method in constructing various optical soliton solutions to the resonant nonlinear Schrodinger equation with both spatio-temporal and inter-modal dispersions. Resonant nonlinear Schrodinger equation expresses the propagation dynamics of optical solitons and Madelung fluids. Dark, bright, combined dark-bright and singular optical solitons are successfully constructed. Under the choice of suitable values of parameters, the two-dimensional, three-dimensional and the contour graphs to some of the acquired results are plotted. The reported results may be useful in explaining the physical meaning of the studied model. (C) 2018 Elsevier GmbH. All rights reserved.
Keywords: ShGEEM; R-NLSE; Kerr law nonlinearity; Optical solitons